GESTIÓN DEL CAMBIO CLIMÁTICO DESDE LA UNIVERSIDAD - Bustamante Dueñas, Yolanda (2012)
Peru is considered the third country in the world most vulnerable to climate change . The university, aware of its leading role in society, has to manage, integrate the government, business and society to achieve sustainability in the short, medium and long term, filling gaps achieving greater social responsibility based on environmental capacity building, information, communication, use of new technologies through teamwork, a shared vision between the different social actors.